Asymmetrical lumbosacral transitional vertebrae in dogs may promote asymmetrical hip joint development - Flückiger, Mark A.; Steffen, Frank; Hässig, Michael; Morgan, Joseph P. (Veterinary and Comparative Orthopaedics and Traumatology, 2017)
Objectives: This study examines the relationship between the morphology of the lumbosacral transitional vertebra (LTV) and asymmetrical development of the hip joints in dogs.Methods: A total of 4000 dogs which had been consecutively scored for canine hip dysplasia were checked for the presence of a LTV. A LTV was noted in 138 dogs and classified depending on the morphology of the transverse processes and the degree of contact with the ilium.Results: In dogs with an asymmetrical LTV, the hip joint was significantly more predis-posed to subluxation and malformation on the side of the intermediate or sacral-like transverse process (p <0.01), on the side of the elevated pelvis (p <0.01), or when an asymmetrical LTV resulted in pelvic rotation on its long axis (p <0.01), whereas hip joint conformation was less affected on the side featuring a free transverse process (p <0.01).Clinical significance: The results support our hypothesis that an asymmetrical LTV favours pelvic rotation over its long axis, resulting in inadequate femoral head coverage by the acetabulum on one side. Inadequate coverage of the femoral head favours subluxation, malformation of the hip joint, and secondary osteoarthritis. Asymmetrical hip conformation may therefore be the sequela of a LTV and mask or aggravate genetically induced canine hip dysplasia.
Keywords: Lumbosacral transitional vertebrae; dog; developmental orthopaedic disorders; diagnostic radiology; hip dysplasia